Literature Review on the Analysis of Effective Tax Rate, Bonus Mechanism, Debt Covenant, and Tax Avoidance on Transfer Pricing - Fatikasari, Riska; Kuntadi, Cris; Pramukty, Rachmat (PT.KARYA GEMAH RIPAH, 2024)
This study aims to examine the factors that influence transfer pricing practices in multinational companies, focusing on four main variables, namely effective tax rate, bonus mechanism, debt covenant, and tax avoidance. The main issue addressed is how these factors can influence transfer pricing decisions, which are often used to reduce tax liabilities and increase corporate profitability. As a solution, this study analyzes relevant literature to identify the relationship between these variables and the application of transfer pricing in multinational companies. The method used is a qualitative literature review, in which the author collected and analyzed data from various journals, books, and related articles obtained from reliable online sources, such as Google Scholar. Through this analysis, this study concludes that each factor studied, namely effective tax rate, bonus mechanism, debt covenant, and tax avoidance, has a significant influence on transfer pricing decisions taken by companies. The results of this study are expected to provide deeper insights into transfer pricing practices, as well as a basis for further research related to other factors that can influence transfer pricing decisions in multinational companies.